Implementasi Social Media Marketing Terhadap Keputusan Pembelian Konsumen pada Rumah Kuning Kecamatan Sinjai Barat - Annisa Nur Awalia; Tenri S.P Dipoatmodjo; M. Ilham Wardhana Haeruddin; Siti Hasbiah; Ilma Wulansari Hasdiansa (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This research aims to determine the impact of Social Media Marketing on purchase decisions at Rumah Kuning in Sinjai Barat District. The data used in this research is primary data with a total of 80 samples. This type of research is classified as quantitative research. The population in this study consists of the consumers of Rumah Kuning in Sinjai Barat District who follow the Rumah Kuning Instagram account. Data collection was carried out using questionnaires and documentation. The method used to analyze the relationship between the independent and dependent variables includes the Classical Assumption Test, namely the Normality Test and Heteroscedasticity Test, Validity Test, Reliability Test, Hypothesis Test (t-test), and Simple Regression Analysis using Statistical Product and Service Solution (SPSS). The results of this study align with (H1), which states that Social Media Marketing has a positive and significant effect on consumer purchase decisions at Rumah Kuning in Sinjai Barat District.